Peningkatan Proses Pembelajaran Menganalisis Unsur Intrinsik Hikayat melalui Model Kooperatif Tipe Jigsaw - Rusnani .; Atmazaki .; Dudung Burhanuddin (Fakultas Bahasa dan Seni UNP, 2013)
Abstract: The purpose of this research is to found the description and the explanation of the developing of student ability. The student’s result of learning in identifikasi of intrigue tale by alsing jigsaw cooperative modeling type of the student class X-5 of SMAN 2 Pangkalan Kerinci. The kind of research is Class Action Research (CAR) that done in three cycle in class X-5 of SMAN 2 Pangkalan Kerinci which is consistent of 24 students. The data was collected by using the observation sheet, field research test. Qualitative data such as, field reserch hope and interviw that were analysised by using the technique of miles and Huberman (1984) and quantitative data, such as observation sheet percentage of Arikunto (1996). The result of research showed that learning by using jigsaw cooperative modeling type be able to developing of the student ability, activity and the students result of class X-5 SMAN 2 Pangkalan Kerinci. Based on the result of percentage data on the thind cycle shaw that the result is better than before which is 90% with KKM is 70 based on the result of research above the conclution that is learning jigsaw cooperative modeling type can develop the student ability, activity and the result of student learning. This happin because jigsaw cooperative modeling type is done through the appropriate procedur ways. By using learning jigsaw cooperative modeling type. The learning material together and they active in discussing to reach out for learning competensi. Kata kunci: proses pembelajaran, menganalisis unsur intrinsik hikayat, model kooperatif tipe jigsaw